Integrated trophic position decreases in more diverse communities of stream food webs - Naoto F. Ishikawa (Nature Portfolio, 2017)
Abstract The relationship between biodiversity and ecosystem functioning is an important theme in environmental sciences. We propose a new index for configuration of the biomass pyramid in an ecosystem, named integrated trophic position (iTP). The iTP is defined as a sum of trophic positions (i.e. the average number of steps involved in biomass transfer) of all the animals in a food web integrated by their individual biomass. The observed iTP for stream macroinvertebrates ranged from 2.39 to 2.79 and was negatively correlated with the species density and the Shannon–Wiener diversity index of the local community. The results indicate a lower efficiency of biomass transfer in more diverse communities, which may be explained by the variance in edibility hypothesis and/or the trophic omnivory hypothesis. We found a negative effect of biodiversity on ecosystem functioning.